AEgIS experiment: towards antihydrogen beam production for antimatter gravity measurements - Mariazzi, Sebastiano; Bräunig, Philippe; Kellerbauer, Alban; Oberthaler, Markus K. (The European physical journal. D, Atomic, molecular, optical and plasma physics, 2014)
AEgIS (Antimatter Experiment: Gravity, Interferometry, Spectroscopy) is an experiment that aims to perform the first direct measurement of the gravitational acceleration g of antihydrogen in the Earth’s field. A cold antihydrogen beam will be produced by charge exchange reaction between cold antiprotons and positronium excited in Rydberg states. Rydberg positronium (with quantum number n between 20 and 30) will be produced by a two steps laser excitation. The antihydrogen beam, after being accelerated by Stark effect, will fly through the gratings of a moiré deflectometer. The deflection of the horizontal beam due to its free fall will be measured by a position sensitive detector. It is estimated that the detection of about 103 antihydrogen atoms is required to determine the gravitational acceleration with a precision of 1%. In this report an overview of the AEgIS experiment is presented and its current status is described. Details on the production of slow positronium and its excitation with lasers are discussed.